2018
DOI: 10.3892/ol.2018.9071
|View full text |Cite
|
Sign up to set email alerts
|

Astragaloside attenuates the progression of prostate cancer cells through endoplasmic reticulum stress pathways

Abstract: Astragaloside (As) has been demonstrated extensively to serve roles in a variety of tumor types, including glioma, lung cancer, colorectal cancer, breast cancer and cervical cancer, and has therefore been widely used in Traditional Chinese Medicine. To the best of our knowledge, the present study was the first to investigate the efficacy of the Traditional Chinese Medicine astragaloside on tumor growth and the apoptosis of prostate cancer cells. In addition, further investigation into the underlying molecular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…The inhibition of CPT1A has been proved to cause ER stress (Schlaepfer et al 2014). Many studies also found that ER stress was involved in apoptosis (Gwak et al 2016;Puthalakath et al 2007;Tan et al 2018). To illuminate the effect of teglicar on ER stress in HeLa cells, the ER stressrelated proteins (GRP78, ATF6, IRE1, PERK, and CHOP) were detected by western blot assay.…”
Section: Discussionmentioning
confidence: 99%
“…The inhibition of CPT1A has been proved to cause ER stress (Schlaepfer et al 2014). Many studies also found that ER stress was involved in apoptosis (Gwak et al 2016;Puthalakath et al 2007;Tan et al 2018). To illuminate the effect of teglicar on ER stress in HeLa cells, the ER stressrelated proteins (GRP78, ATF6, IRE1, PERK, and CHOP) were detected by western blot assay.…”
Section: Discussionmentioning
confidence: 99%
“…Besides the interplay between ER and mitochondrial intrinsic apoptosis pathway, activation of ER-resident caspase, during ER stress, represents another mechanism to induce apoptosis. Indeed, under ER stress, the active form of rodent caspase-12 and human caspase-4 activates caspase-9, which in turn activates caspase-3, triggering apoptosis [ 41 ].…”
Section: Er Stress Mediates Upr For Anticancer Strategiesmentioning
confidence: 99%
“…Previous studies have confirmed the beneficial effects of AS-IV in the therapy of many diseases, including fibrosis, inflammatory, autoimmune and cardiovascular diseases [5,6]. Previous showed that AS-IV is valuable for cancer treatment due to its inhibitory effects on the proliferation, invasion and metastasis in various tumours, such as prostate cancer [7], breast cancer [8], gastric cancer [9], lung cancer [10] and glioma [11]. However, the effects of AS-IV on the invasion and metastasis in VSCC remain unclear.…”
Section: Introductionmentioning
confidence: 83%